CWSP guide to wireless security (Thomson Course Technology, 2007)
"CWSP Guide to Wireless Security is a hands-on guide to defending wireless networks against attacks. This book prepares students for the Certified Wireless Security Professional (CWSP) certification from Planet3. Focusing on IEEE 802.11a/b/g/pre-n wireless local area networks, this book provides extensive coverage of the latest wireless attack tools and defenses, including IEEE 802.11i, WPA, WPA2, and WIPS, along with how to design and manage a secure wireless LAN. Material is reinforced with hands-on projects at the end of each chapter."